More Active Intestinal Immunity Developed by Obese Mice Than Non-Obese Mice After Challenged by Escherichia coli - Cai, Dongjie; Tian, Bin; Liang, Shuang; Cen, Yao; Fang, Jing; Ma, Xiaoping; Zhong, Zhijun; Ren, Zhihua; Shen, Liuhong; Gou, Liping; Wang, Ya; Zuo, Zhicai (Frontiers in Veterinary Science, 2022)
Obese mice presented lower mortality to the non-fatal pneumonia induced by Escherichia coli (E. coli) than the non-obese mice. However, it remained obscure whether the intestine contributed to the protective effect of obese mice with infection. The 64 non-obese mice were divided into group I and II, while 64 high-fat diet-induced obesity mice (DIO) were divided into group III and IV. Mice in groups I and III were intranasally infused with 40 µl phosphate buffer saline, while mice in groups II and IV were intranasally infused with the same volume of E. coli (4.0×109 CFU). The T lymphocyte subsets of epithelium (IELS) and lamina propria (LPLs) in intestine were collected to analyze through flow cytometry at 0 h, 12 h, 24 h and 72 h post-infection, and the duodenum and colon were harvested to survey histopathological change. The results showed that the percentage of CD3+T cells in intestinal LPLs in group IV was significantly lower than that in group III after infection (p<0.05). The percentage of CD4+T cells in intestinal IELs in group II was significantly lower than that in group IV after infection (p<0.05). The percentage of CD8+T cells in LPLs in group II was significantly lower than that in group IV at 12 h and 24 h (p<0.05). The number of IgA+ cells in group III was higher than that in group I at all time points (p<0.05). The number of IgA+ cells in group IV was higher than that in group III at 12 h, 24 h and 72 h post-infection (p<0.05). The results revealed that the level of intestinal mucosal immunity in obese mice was more active than that in non-obese mice.